Airport systems : planning, design, and management - De Neufville, Richard, 1939-; Odoni, Amedeo R.; Belobaba, Peter; Reynolds, Tom (New York : McGraw-Hill, 2013)
'This is a premier text by leading technical professionals, known worldwide for their expertise in the planning, design, and management of airports'-Provided by publisher.
Includes bibliographical references and index.
Keywords: Airports -- Planning; Airports -- Design and construction; Airports -- Management